Main Features Of Speech Acts And Their Place In Modern Linguistics (Eurasian Journal of Humanities and Social Sciences, 2026)
This article examines the concept of speech acts and their significance in modern linguistics. Speech acts represent one of the central aspects of communication because language is used not only to convey information but also to perform actions such as requesting, apologizing, promising, and advising. The purpose of this study is to analyze the theoretical foundations, classifications, and communicative functions of speech acts within contemporary linguistic research. The article applies descriptive and analytical methods to investigate how speech acts operate in spoken interaction and how they contribute to pragmatic meaning. The findings demonstrate that speech act theory occupies an important place in modern linguistics due to its connection with pragmatics, discourse analysis, and intercultural communication. The study concludes that speech acts reflect the relationship between language, intention, and social interaction.